Quantum governance : rewiring the foundation of public policy - Farra, Fadi; Pissarides, Christopher (Emerald Publishing Limited, 2023)
What does "development' mean? How does "progress' happen? What drives civilisational change, from the first urban settlements in Mesopotamia to the creation of the first green smart cities? From the first agricultural exploitations to the knowledge economy? How did we, as a human community, build the world as we know it and what will define the next steps of our journey on earth? Asking fundamental questions has long been out of fashion for individuals in general, let alone for policymakers. But, fundamental "why' questions play with the boundaries and define them. Crises offer a window of opportunity, a small time-bubble during which people are collectively drawn to understanding what went wrong, asking what is it that brought us here. If there ever was a time to initiate this long overdue process of asking and reflecting on the questions that matter, today, in the middle of an unprecedented crisis, is it. We call for the adoption of a citizen-centric networked approach to development that meaningfully incorporates individual needs and wellbeing while shifting the focus away from economic growth as the only relevant parameter.